Dopamine-Induced Changes in Gαolf Protein Levels in Striatonigral and Striatopallidal Medium Spiny Neurons Underlie the Genesis of l-DOPA-Induced Dyskinesia in Parkinsonian Mice - Morigaki, Ryoma; Okita, Shinya; Goto, Satoshi (Frontiers in Cellular Neuroscience, 2017)
The dopamine precursor, l-3,4-dihydroxyphenylalanine (l-DOPA), exerts powerful therapeutic effects but eventually generates l-DOPA-induced dyskinesia (LID) in patients with Parkinson’s disease (PD). LID has a close link with deregulation of striatal dopamine/cAMP signaling, which is integrated by medium spiny neurons (MSNs). Olfactory type G-protein α subunit (Gαolf), a stimulatory GTP-binding protein encoded by the GNAL gene, is highly concentrated in the striatum, where it positively couples with dopamine D1 (D1R) receptor and adenosine A2A receptor (A2AR) to increase intracellular cAMP levels in MSNs. In the striatum, D1Rs are mainly expressed in the MSNs that form the striatonigral pathway, while D2Rs and A2ARs are expressed in the MSNs that form the striatopallidal pathway. Here, we examined the association between striatal Gαolf protein levels and the development of LID. We used a hemi-parkinsonian mouse model with nigrostriatal lesions induced by 6-hydroxydopamine (6-OHDA). Using quantitative immunohistochemistry (IHC) and a dual-antigen recognition in situ proximity ligation assay (PLA), we here found that in the dopamine-depleted striatum, there appeared increased and decreased levels of Gαolf protein in striatonigral and striatopallidal MSNs, respectively, after a daily pulsatile administration of l-DOPA. This leads to increased responsiveness to dopamine stimulation in both striatonigral and striatopallidal MSNs. Because Gαolf protein levels serve as a determinant of cAMP signal-dependent activity in striatal MSNs, we suggest that l-DOPA-induced changes in striatal Gαolf levels in the dopamine-depleted striatum could be a key event in generating LID.